Flawed cloud architectures and the rise of decentral alternatives - Primavera De Filippi (Internet Policy Review, 2013)
The high degree of centralisation that characterises many cloud-based services raises a series of challenges in terms of (a) security, due to there being only a few points of failure or attack, (b) privacy, due to the users' lack of control over the collection and use of personal data, and (c) user autonomy, given that users increasingly depend on third parties services and infrastructures. After analysing the drawbacks of traditional cloud computing platforms, this article provides an overview of how civil society is progressively challenging the centralised cloud establishment by providing decentralised alternatives to cloud computing which could potentially help overcome these drawbacks.
Keywords: 300; Cloud computing; IT system architecture; Informational self-determination; Decentralisation; Infrastructure as a Service (IaaS); Autonomy; Centralisation; Privacy